Injectable semaglutide and reductions in HbA1c and weight in the real world in people switched from alternative glucagon‐like peptide‐1 receptor agonists. Issue 7 (7th April 2022) - Crabtree, Thomas S. J.; Adamson, Karen; Reid, Hazel; Barnes, Dennis; Sivappriyan, Siva; Bickerton, Alex; Gallen, Ian W.; Field, Benjamin C. T.; Idris, Iskandar; Ryder, Robert E. J.; ,
Abstract: The ABCD semaglutide audit was designed to capture the routine clinical outcomes of people commenced on semaglutide in the UK. Previous work showed differential reductions in HbA1c and weight dependent on previous glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) exposure. The analysis, in this research letter, shows that decreases in HbA1c and weight associated with semaglutide occur irrespective of previous GLP‐1RA use. However, HbA1c reductions were less if switched from dulaglutide or liraglutide and weight changes were attenuated if switched from dulaglutide or exenatide, potentially suggesting differing potencies between GLP‐1RAs. Dedicated studies with head‐to‐head comparisons are needed to confirm these findings.